Retention of female volunteer community health workers in Dhaka urban slums: a case-control study - Alam, Khurshid; Tasneem, Sakiba; Oliveras, Elizabeth (2016)
This article was published in The Journal of Health Policy and Planning [©2012 Published by Oxford Journal] and the definite version is available at: http://doi.org/10.1093/heapol/czr059 The Article's website is at: http://heapol.oxfordjournals.org/content/27/6/477